'They have a go at me, that I'm a good English guy. Well, I'm Polish as well': how bilingual Polish adolescents in the UK negotiate the position of 'linguistic expert'. Issue 1 (2nd January 2022) - Young, Sara
ABSTRACT: This paper explores the position of 'linguistic expert', and how being positioned as an expert affects the linguistic and ethnic identity construction of a group of Polish-English bilingual adolescents living in the UK. Findings indicate that while the participants are often positioned as linguistic experts in English and/or Polish, this may not correspond with their own feelings of linguistic competency. In the UK, the adolescents engage in language brokering, a practice which presumes an expert knowledge of each language that the participants do not always feel they possess. At school, the adolescents resist being regarded as fluent in English; when visiting Poland, they find their knowledge of Polish lacking. Closer examination of the participants' narratives suggests that the concept of linguistic 'expert' is open to negotiation, and that the adolescents both challenge and exploit notions of expertise as they negotiate their own linguistic and ethnic identities.